Studi Analisis Tingkat Pengeluaran Konsumsi Rumah Tangga di Kalimantan Barat: Implikasi terhadap Pertumbuhan Ekonomi Regional: (Analysis Study of Household Consumption Expenditure Levels in West Kalimantan: Implications for Regional Economic Growth) - Supriaman, Supriaman; Mubaraq, Abd. (UPT Penerbitan Universitas Jember, 2024)
The amount that households spend on consumption determines a region's economic growth rate. This study examines the connection between household consumption spending and economic expansion in West Kalimantan's districts and cities. Panel data regression is the analytical technique used to consider regional variances. The Central Statistics Agency (BPS) and other relevant organizations were among the data sources used in this study. The dependent variable is economic growth, and the independent variable is household consumption spending. The analysis's findings demonstrate that household consumption spending and economic growth in West Kalimantan Province's districts and cities are positively and significantly correlated. This clarifies why raising household consumption expenditures has advantages.